Emerging Biomedical Applications of Algal Polysaccharides - Rahmati, Maryam; Alipanahi, Zahra; Mozafari, Masoud (Current Pharmaceutical Design, 2019)
Background: Over the past two decades, there have been substantial progress and a growing body of research on using natural polymeric biomaterials in emerging biomedical applications. Among different natural biopolymers, polysaccharides have gained considerable attraction among biomedical scientists and surgeons due to their biocompatibility, biodegradability, anti-inflammatory, and antimicrobial properties. In recent years, algalbased polysaccharides including agar, alginate, and carrageenan, have been broadly suggested for different biomedical applications. Methods: The aim of this paper is discussing various possible applications of algal-based polysaccharides in biomedical engineering particularly in controlled drug delivery systems. The main properties of each algal polysaccharide will be discussed, and particular drug delivery applications will be presented. Results: Algal polysaccharides can be detected in a group of photosynthetic unite as their key biomass constituents. They provide a range of variety in their size, shape, liquefaction, chemical stability, and crosslinking ability. In addition, algal polysaccharides have shown exceptional gelling properties including stimuli-responsive behavior, softness, and swelling properties. Conclusion: All the mentioned properties of alga polysaccharides lead to their successful usage in biomedical applications specially targeted and controlled drug delivery systems such as particles, capsules, and gels.
Keywords: drug delivery